The daring ladies of Lowell [large type] - Alcott, Kate (Center Point Large Print, 2014)
Moving to the mill city of Lowell in 1832 to escape farm life, young Alice is disillusioned by the local factory's harsh working conditions and struggles to advocate on their behalf while recklessly falling in love with the mill owner's son, a situation that is complicated by a murder and sensational trial.